Enhanced Prostacyclin Synthesis by Adenoviral Gene Transfer Reduced Glial Activation and Ameliorated Dopaminergic Dysfunction in Hemiparkinsonian Rats. (3rd April 2013) - Tsai, May-Jywan; Weng, Ching-Feng; Yu, Nien-Chu; Liou, Dann-Ying; Kuo, Fu-San; Huang, Ming-Chao; Huang, Wen-Cheng; Tam, Kabik; Shyue, Song-Kun; Cheng, Henrich
Abstract : Prostacyclin (PGI2 ), a potent vasodilator and platelet antiaggregatory eicosanoid, is cytoprotective in cerebral circulation. It is synthesized from arachidonic acid (AA) by the sequential action of cyclooxygenase- (COX-) 1 or 2 and prostacyclin synthase (PGIS). Because prostacyclin is unstable in vivo, PGI2 analogs have been developed and demonstrated to protect against brain ischemia. This work attempts to selectively augment PGI2 synthesis in mixed glial culture or in a model of Parkinson's disease (PD) by direct adenoviral gene transfer of prostacyclin biosynthetic enzymes and examines whether it confers protection in cultures or in vivo . Confluent mixed glial cultures actively metabolized exogenous AA into PGE2 and PGD2 . These PGs were largely NS398 sensitive and considered as COX-2 products. Gene transfer of AdPGIS to the cultures effectively shunted the AA catabolism to prostacyclin synthesis and concurrently reduced cell proliferation. Furthermore, PGIS overexpression significantly reduced LPS stimulation in cultures. In vivo, adenoviral gene transfer of bicistronic COX-1/PGIS to substantia nigra protected 6-OHDA- induced dopamine depletion and ameliorated behavioral deficits. Taken together, this study shows that enhanced prostacyclin synthesis reduced glial activation and ameliorated motor dysfunction in hemiparkinsonian rats. Prostacyclin may have a neuroprotective role in modulating the inflammatory response in degenerating nigra-striatal pathway.